1990
DOI: 10.1080/02815739008730221
|View full text |Cite
|
Sign up to set email alerts
|

Networks in urban neighbourhoods: Lost, saved or liberated communities?

Abstract: Schiefloe, Per Morten: Networks in urban neighbourhoods: lost, saved or liberated communities? SHPR 7: 93-103, 1990. The article presents theories and empirical findings on social relations in urban neighbourhoods. It briefly puts the tradition of neighbourhood studies into the history of mainstream sociology, especially concerning the question of community. The overview of studies of locally based social relations is organized in terms of the hypotheses of urban communities as being lost, saved or liberated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
8

Year Published

1994
1994
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 6 publications
0
9
0
8
Order By: Relevance
“…Aroian (: 180 f) suggested that weak ties in the neighbourhood may be poor sources of emotional support but best for helping immigrants learn new roles. Bridge () and Schiefloe () emphasised the ‘strength of weak ties’ in a sense that even small gestures of recognition of one's neighbours, which one may classify as ‘nodding relationships’ can be important for migrants in a process of social integration. It is not only the strength of contacts that matters for fostering attachment to the neighbourhood but also with whom ties are made and how they are connected through the neighbourhood (Hipp & Perrin, ).…”
Section: Theoretical Perspectives On Place Attachment and Its Determimentioning
confidence: 99%
“…Aroian (: 180 f) suggested that weak ties in the neighbourhood may be poor sources of emotional support but best for helping immigrants learn new roles. Bridge () and Schiefloe () emphasised the ‘strength of weak ties’ in a sense that even small gestures of recognition of one's neighbours, which one may classify as ‘nodding relationships’ can be important for migrants in a process of social integration. It is not only the strength of contacts that matters for fostering attachment to the neighbourhood but also with whom ties are made and how they are connected through the neighbourhood (Hipp & Perrin, ).…”
Section: Theoretical Perspectives On Place Attachment and Its Determimentioning
confidence: 99%
“…However, over time additional network studies of neighborhoods found that urbanites’ motivation to engage in local networks varies in response to their alternative sources for social relations and network involvement (Fischer, 1982). Within the structure created by relationships and the resulting opportunities to meet other people, involvement with potential new network members is both selective and quantitatively limited (Schiefloe, 1990: 99). The increased geographic reach of ties among urban residents and the absence of simple hierarchical group structures create spatially and socially ramified networks (Wellman, 1999).…”
Section: Gendered Immigrant Incorporation In New Urban Spacesmentioning
confidence: 99%
“…Au sein de la diversité des échanges qui ont cours dans les processus de socialisation, le lien de responsabilité attire particulièrement l'attention : dans un contexte de mutations, c'est-à-dire d'imprévisibilité et de risques, il devient pertinent puisque la responsabilité est la capacité de répondre à des individus et à des institutions dans un contexte d'indétermination voire de contingence (Bauman, 1998 (Charbonneau, 1998). Le lien social n'est plus fondé sur la solidarité organique d'une communauté telle que l'entendait Tönnies à propos des communautés rurales, par exemple (Schiefloe, 1990). Mais même s'il est tentant de se concentrer sur l'individuation du lien social, vu l'intérêt de la sociologie pour les liens sociaux modernes, il faut garder à l'esprit que les traditions ou les normes ne disparaissent pas, elles se diversifient (Giddens, 2000).…”
Section: Un Contexte De Mutations Socialesunclassified